Pharmacokinetics of felodipine extended-release tablets in healthy Taiwanese subjects: a retrospective review - Chia-Ling, Hsiao; Ya-Chi, Wu; Kuang-Yang, Hsu (Arzneimittelforschung, 2011)
The objective of this study was to investigate the pharmacokinetics of felodipine (CAS 72509-76-3) in healthy male Taiwanese subjects. This is a retrospective review of five felodipine pharmacokinetic studies completed in Taiwan. A total of 100 evaluable healthy Taiwanese males were enrolled in these studies. The subjects received 5 mg (n = 80) or 10 mg (n = 20) of Plendil® (felodipine extended-release tablets; felodipine ER) once daily for 6 days. The mean ± SD tmax, ss, Cmax, ss and AUCτ of dose normalized to 10 mg felodipine was 3.32 ± 1.33 h, 13.12 ± 5.34 nmol/L and 136.33 ± 63.18 nmol · h/L, respectively. By using Kolmogorov-Smirnov’s test and probit plots, the results indicated that the frequency distribution of AUC/dose, Cmin/ dose and CL/F was bimodal. Compared to data from the literature, the mean Cmax, ss and AUCτ of 5 mg felodipine in healthy young Taiwanese subjects were similar to or slightly lower than data from Swedish, Danish, Turkish and Canadian studies in healthy young subjects who received 10 mg felodipine. Comparable Cmax values and approximately 30% lower AUC values were observed when comparing the 5 mg Taiwanese data to data in healthy elderly German subjects who also received 5 mg felodipine. Taiwanese subjects might have lower CYP3A4 activity to metabolize felodipine, which is similar to the phenomenon observed with nifedipine.
Keywords: Antihypertensive drug; Calcium-channel blocker; Felodipine; Pharmacokinetics; Taiwanese